Ginger Shaft as Novel Adsorbent for Chromium (VI) Removal: Kinetics and Adsorption Isotherms - OSENI, M. O.; ADESEMUYI, M. F.; OGUNDELE, J. O.; OLADUGBA, O. A.; ADEBAYO, A. O.; LAJIDE, L. (Journal of Science, Technology and Innovation Research, 2026)
The potential of ginger shaft in adsorbing Chromium metal (Cr6+) ions from aqueous solution was examined in this study. Fine particles of adsorbent were used in determining the adsorption isotherm of chromium ion. It was observed that the rate of adsorption increased significantly for chromium between 40 – 60 mins of contact time. There was a sharp increase in adsorption of chromium ions between the pH of 1 – 3 given the maximum adsorption at 98.77%. It was expected that an increase in the adsorbent dosage should yield a corresponding increase in the amount of metal ions adsorbed into the surface of the adsorbent since there will be more site for the adsorbate to be adsorbed. The trend was consistent, which suggests that the use of ginger shaft as adsorbent fully depends on its dosage in aqueous solution. The result of adsorption due to temperature was inconsistent. There was a progress increase in the percentage adsorption as the adsorbate concentration increases. The adsorption of the chromium ions on ginger shaft correlate with the known Freundlich adsorption isotherms with chromium having better adsorption onto the adsorbent because it does have a straight-line graph and the value of the slope is 1/n which is greater than 1. This infers that n is less than 1, which does not correlate with Langmuir sorption isotherm because it does not have a straight-line graph. Therefore, ginger can be used in the treatment of polluted wastewater to adsorb Chromium ion. KEY WORDS: Ginger shaft, adsorbent dosage, pH, temperature, contact time, chromium